Citrus sinensis MYB Transcription Factor CsMYB85 Induce Fruit Juice Sac Lignification Through Interaction With Other CsMYB Transcription Factors - Jia, Ning; Liu, Jiqin; Tan, Penghui; Sun, Yufeng; Lv, Yuemeng; Liu, Jiameng; Sun, Jing; Huang, Yatao; Lu, Jia; Jin, Nuo; Li, Minmin; Md Sharif Uddin Imam, Khandaker; et al. (Frontiers in Plant Science, 2019)
Citrus is an important fruit worldwide. It is valued for being highly nutritious and having an appealing flavor. Lignification of citrus fruit juice sacs is a serious physiological disorder which occurs during postharvest storage. However, their transcriptional regulation mechanisms remains unclear. In the present study, the potential involvement of a MYB transcription factor, CsMYB85, was identified and isolated and found that it has homologs in Arabidopsis and other plants. All of these regulate lignin biosynthesis. During juice sac lignification, CsMYB85 expression levels significantly increase. Therefore, this gene may control lignin biosynthesis. The results indicated that CsMYB85 binds CsMYB330 promoter, regulates its expression, and interacts with CsMYB308 in yeast and tobacco. A transient assay indicated that Cs4CL1 expression levels and lignin content were significantly increased in fruit juice sacs overexpressing CsMYB85. At4CL1 expression levels and lignin content were also significantly increased in Arabidopsis overexpressing CsMYB85. Therefore, the CsMYB85 transcription factors participate in fruit juice sac lignification. This study provides a new insight into the transcriptional regulation of citrus fruit juice sac lignification.